Un caso studio di analisi geospaziale applicata alla mobilità ciclistica: l'analisi dei flussi della città di Napoli (GEOmedia, 2017)
In May 2015, the City of Naples and forty others European cities have joined the fourth edition of the European Cycling Challenge. This event has been created to promote the bicycle as a sustainable transport mean in urban areas, and lasted for all the month of May.The event organizer, SRM Reti e Mobilità , provided an app where all citizens/cyclists could enroll and track their cycle journeys; the app was tracking, with a time interval of five seconds, the cyclist position (using GPS) and some journey details (journey name, length, speed, besides day and schedule).These data were registered by the app and saved in a database. Several months after the event, each database has been sent to the participating cities.Naples' database has been utilized to evaluate, for the first time, the cycling mobility in the city. Indeed, the City of Naples developed a cycle network longer than twenty kilometers in the recent years. Therefore, this evaluation aimed to understand how, when and where the cyclists have been using these paths.The evaluation required the development of a methodological framework to analyze the database in geospatial environment.The final product has been disaggregated in two categories, the territorial evaluation and the temporal evalua-tion.The territorial evaluation contains O-D matrices, an analysis involving Naples' districts, and a flow count analysis for road. The temporal evaluation includes an analysis for each day of the month, for each day of the week (Monday, Tuesday,and so on), and for two time slots (7,30 – 9,30 A.M. and 4,30 – 6,30 P.M.).The overall results registered over 7961 kilometers covered and 1308 registered trips, with an average journey length of 6,07 kilometers and a massive use of the Waterfront cycle path (Via Francesco Caracciolo and ViaPartenope).